Utility of three novel insulin resistance‐related lipid indices for predicting type 2 diabetes mellitus among people with normal fasting glucose in rural China: 在空腹血糖正常的中国农村人群中使用3种新的胰岛素抵抗相关血脂指标来预测2型糖尿病. Issue 8 (9th February 2018) - Wang, Bingyuan; Zhang, Ming; Liu, Yu; Sun, Xizhuo; Zhang, Lu; Wang, Chongjian; Li, Linlin; Ren, Yongcheng; Han, Chengyi; Zhao, Yang; Zhou, Junmei; Pang, Chao; et al.
Abstract: Background: Inexpensive and easily measured indices are needed for the early prediction of type 2 diabetes mellitus (T2DM) in rural areas of China. The aim of this study was to compare triglyceride glucose (TyG), visceral adiposity (VAI), and lipid accumulation product (LAP) with traditional individual measures and their ratios for predicting T2DM. Methods: Data for 11 113 people with baseline normal fasting glucose in a rural Chinese cohort were followed for a median of 6.0 years. Cox proportional hazards regression was used to calculate covariate‐adjusted hazard ratios (aHRs) and 95% confidence intervals (95% CIs) and receiver operating characteristic analysis was used to compare the ability of traditional measures and TyG, VAI, and LAP at baseline to predict T2DM at follow‐up. Results: Among individual measures, fasting plasma glucose (FPG) and waist circumference (WC) were strongly associated with T2DM. Of all lipid ratios, an elevated triglycerides (TG) to high‐density lipoprotein cholesterol (HDL‐C) ratio was associated the most with T2DM. Compared with the first quartiles of TyG, VAI, and LAP, their fourth quartiles were associated with T2DM for men (aHR 3.54 [95% CI 2.08–6.03], 2.89 [1.72–4.87], and 5.02 [2.85–8.85], respectively) and women (6.15 [3.48–10.85], 4.40 [2.61–7.42], and 6.49 [3.48–12.12], respectively). For predicting T2DM risk, TyG, VAI, and LAP were mostly superior to the TG: HDL‐C ratio, but did not differ from FPG and WC. Conclusions: Prediction of T2DM was not improved by TyG, VAI, and LAP versus FPG or WC alone. Therefore, TyG, VAI, and LAP may not be inexpensive tools for predicting T2DM in rural Chinese people. Abstract : Highlights Data are limited regarding the prevention of type 2 diabetes mellitus (T2DM) in rural Chinese people. Elevated triglyceride glucose, visceral adiposity, and lipid accumulation product are significantly associated with the risk of incident T2DM. Triglyceride glucose, visceral adiposity, and lipid accumulation product did not improve the T2DM prediction compared with fasting plasma glucose or waist circumference.